Angola: ação diplomática brasileira no processo de independência dos países africanos em conflito com Portugal no cenário da Guerra Fria - Santos, José Francisco dos (2015)
This research had as finality to reflect about the relation Brazil and Angola in the diplomatic, economic, social and cultural aspects, through a documentation of the Itamaraty and bibliography pertinent to the period between 1974 until the current days. We observed that the work is going to concentrate itself in the report produced by the Brazilian embassy in Lisbon, in the year of 1974, to the Brazilian Ministry of Exterior Relations regarding the Carnation Revolution and, mainly, the situation of the independence processes of the African countries, which, until that moment, were called Overseas Provinces . We registered in the following year the diplomatic documents produced mainly by the Brazilian Representation in Angola throughout the year of 1975, led by the diplomat Ovídeo de Andrade Melo. In a second moment, we analyzed the documents of the Itamaraty from 1976 until 1983. The other periods are covered by bibliography and depositions concerning the relation Brazil and Angola